Protocol for a case–control prospective study to investigate the impact of Hepatic Encephalopathy on Nutritional Intake and Sarcopenia status in patients with end-stage LIVer disease: HENS-LIV study - Jennifer Towey; Chiemelie Ngonadi; Neil Rajoriya; Andrew Holt; Carolyn Greig; Matthew J Armstrong (BMJ Open Gastroenterology)
Introduction Hepatic encephalopathy (HE) is a debilitating symptom of end-stage liver disease (ESLD), but there remains a paucity of evidence regarding its impact on nutritional status, nutritional intake, compliance with nutritional support and resultant muscle health and function. Malnutrition and sarcopenia are associated with increased morbidity and mortality in patients with ESLD. The aim of the current case–control study is to prospectively investigate the impact of HE on nutritional intake and sarcopenia status in patients with ESLD.Methods and analysis Patients with ESLD, with HE (n=10) and without HE (n=10) will be recruited at the outpatient liver unit, University Hospital Birmingham, UK. All patients will undergo clinical assessment at baseline and again at 6–8 weeks (in-line with their routine clinical follow-up), to assess the impact of HE on reported nutritional intake, nutritional status and sarcopenia/physical functional status. Standard medical, dietetic and home-based exercise physiotherapy care will continue for all participants as determined by their clinical team. Two methods of assessing nutritional intake will include the 24-hour food recall and 3-day food diaries. Assessment of sarcopenia status will be undertaken using anthropometry (mid-arm muscle circumference (MAMC)) and ultrasound imaging of the quadriceps muscle group. Markers of physical function (hand grip strength; chair rise time), frailty (Liver Frailty Index (LFI)), physical activity (accelerometery) and exercise capacity (Duke Activity Status Index (DASI)) will be assessed at both clinic visits.Ethics and dissemination The study is approved by Wales Research Ethics Committee 2 and Health Research Authority (REC reference: 21/WA/0216). Recruitment into the study commenced November 2021. The findings will be disseminated through peer-reviewed publications and international presentations.Trial registration number RRK7156.